Atypical Porcine Pestivirus (APPV) as a New Species of Pestivirus in Pig Production - Gatto, Igor Renan Honorato; Sonálio, Karina; de Oliveira, Luís Guilherme (Frontiers in Veterinary Science, 2019)
The genus Pestivirus, which belongs to the family Flaviviridae, includes ssRNA+ viruses responsible for infectious diseases in swine, cattle, sheep, goats, and other domestic and wild animals. Recently, several putative pestiviruses species have been discovered and characterized in mammalian species (giraffe pestivirus, antelope pestivirus, HoBi virus, Bungowannah virus, and Linda virus); one of these is a genetically distinct pestivirus, named atypical porcine pestivirus (APPV), discovered using the next-generation sequencing technology. APPV has been detected in piglets with congenital tremor (CT) from four different continents, including North America, South America, Europe, and Asia. There is strong evidence that experimental inoculation and in field outbreaks involving APPV induce CT in piglets. Additionally, splay leg (SL) syndrome has been observed concurrently with CT, and it was induced by APPV in experimental studies and some field cases. Animals with a persistent and/or chronic infection condition can shed the virus over time. Viral-RNA is frequently detected in different tissues from CT-piglets; however, high loads of APPV are detected most consistently in central nervous tissue. Moreover, the APPV genome has been recently detected in semen and preputial swabs from boar studs, as well as in serum and tissue samples from wild boars and domestic adult pigs, all known to be clinically healthy. Phylogenetic analysis revealed that the APPV sequence (complete or partial polyprotein) exhibits high genetic diversity between viral strains detected in different countries and formed independent clusters according to geographic location. Additional studies are needed to evaluate the molecular detection and sero-prevalence of APPV around the world. Lastly, more research is needed to understand clinical presentations associated with APPV infection, as well as the economic losses related to the virus in pig production worldwide.